Correlation Between Computed Tomography Features and Clinical Presentation and Management of Isolated Superior Mesenteric Artery Dissection. (December 2018) - Zhang, Xiaoling; Xiang, Pei; Yang, Yanhong; Chen, Jiawen; Guan, Jian; Liu, Mingjuan; Guo, Yan; Wang, Huanjun; Li, Shurong; Sun, Canhui
Abstract : Objectives: To examine the correlation between computed tomography (CT) features and clinical presentation and to assess the management strategy for patients with isolated superior mesenteric artery (SMA) dissection. Material and methods: Retrospective analysis of clinical records and CT findings of patients with isolated superior mesenteric artery dissection treated between 2012 and 2016. The relationship between CT features and clinical symptoms and treatment options was studied. Follow up CT images were reviewed and telephone interviews were conducted with patients. Results: Sixty-nine patients with isolated SMA dissection (47 symptomatic and 22 asymptomatic) were evaluated. The dissection length in patients with Sakamoto type IV lesions was significantly longer than that in patients with other lesion types (83.0 ± 40.1 mm, p  = .001). Compared with the asymptomatic group, the symptomatic group had longer dissections (63.5 ± 35.9 mm, p  < .001) and lesser true lumen diameter (3.1 ± 1.7 mm, p  = .044). Fifty-six patients were treated conservatively, of whom 31 showed clinical improvement and exhibited no morphological change during long-term follow up. Conclusions: In patients with isolated SMA dissection, clinical symptoms were related to the length of dissection and degree of true lumen stenosis. Conservative treatment was commonly employed and yielded favourable outcomes.